Congenital Toxoplasmosis in a 15 Day-Old Infant a Case Report - Sri Rezeki Harun; Evita K. Saleh; Srisasi Gandahusada; Chairil Hamdani (Indonesian Pediatric Society, 1989)
A case of congenital toxoplasmosis in a 1 5-day old infant was reported, citing the difficulties encountered in establishing the diagnosis due to the wide range of the disease's clinical spectrum. Congenital toxoplasmosis was suspected after finding hydrocephalus, cerebral calcification, and chorioretinitis. Serology tests with the ELISA technique were highly positive for antibodies against lgG, whereas anti-IgM was negative. The patient died before the second serological analysis was done. The final diagnosis of congenital toxoplasmosis was eventually established at autopsy, based on the detection of T. gondii in the brain, testicular, liver, spleen and striated muscle tissues.